Analisis Potensi Produk Kue Kering UMKM Tintun’s Cookies Dalam Menembus Pasar Global - Lilik Nurul Wahidah (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
Tintun's Cookies, an SMEs of pastry and cookies that has been established for more than 10 years, plans to expand overseas. This study aims to identify countries with potential for Tintun's Cookies products, analyse external and internal factors, and formulate appropriate export strategies for Tintun's Cookies in preparing for exports to the target country. The research method uses Market Research Analysis using Trademap data and indicators such as import tariffs, requirements, trends, and distance in the destination country, PESTEL, EFE, IFE, and Marketing Mix 7ps. The results of the study show that Malaysia is the recommended country to be the main export destination for Tintun's Cookies products. This is supported by high market demand, proximity, elimination of import tariffs, ease of regulation, and cultural and product trend similarities. Based on the intersection of the IFE and EFE matrices, it shows that Tintun's Cookies is in quadrant 1, namely Grow and Build, where this position shows that Tintun's Cookies is in good condition in terms of strengths and opportunities and has the capability to export cookies to Malaysia. Thus, it is recommended a marketing strategy to take advantage of opportunities by developing products, market penetration, and market development. Some of the proposed strategies are to meet export requirements in Indonesia and Malaysia through export training from the government, meet labelling and identity requirements for cookies in Malaysia, set competitive selling prices, collaborate with the government and e-commerce media to reach consumers.